Preventive or Deferred Ablation of Ventricular Tachycardia in Patients With Ischemic Cardiomyopathy and Implantable Defibrillator (BERLIN VT): A Multicenter Randomized Trial. Issue 13 (31st March 2020) - Willems, Stephan; Tilz, Roland Richard; Steven, Daniel; Kääb, Stefan; Wegscheider, Karl; Gellér, László; Meyer, Christian; Heeger, Christian-Hendrik; Metzner, Andreas; Sinner, Moritz F.; Schlüter, Michael; Nordbeck, Peter; et al.
Abstract : Background: Catheter ablation for ventricular tachycardia (VT) reduces the recurrence of VT in patients with implantable cardioverter-defibrillators (ICDs). The appropriate timing of VT ablation and its effects on mortality and heart failure progression remain a matter of debate. In patients with life-threatening arrhythmias necessitating ICD implantation, we compared outcomes of preventive VT ablation (undertaken before ICD implantation to prevent ICD shocks for VT) and deferred ablation after 3 ICD shocks for VT. Methods: The BERLIN VT study (Preventive Ablation of Ventricular Tachycardia in Patients With Myocardial Infarction) was a prospective, open, parallel, randomized trial performed at 26 centers. Patients with stable ischemic cardiomyopathy, a left ventricular ejection fraction between 30% and 50%, and documented VT were randomly assigned 1:1 to a preventive or deferred ablation strategy. The primary outcome was a composite of all-cause death and unplanned hospitalization for either symptomatic ventricular arrhythmia or worsening heart failure. Secondary outcomes included sustained ventricular tachyarrhythmia and appropriate ICD therapy. We hypothesized that preventive ablation strategy would be superior to deferred ablation strategy in the intention-to-treat population. Results: During a mean follow-up of 396±284 days, the primary end point occurred in 25 (32.9%) of 76 patients in the preventive ablation group and 23 (27.7%) of 83 patients in the deferred ablation group (hazard ratio, 1.09 [95% CI, 0.62–1.92]; P =0.77). On the basis of prespecified criteria for interim analyses, the study was terminated early for futility. In the preventive versus deferred ablation group, 6 versus 2 patients died (7.9% versus 2.4%; P =0.18), 8 versus 2 patients were admitted for worsening heart failure (10.4% versus 2.3%; P =0.062), and 15 versus 21 patients were hospitalized for symptomatic ventricular arrhythmia (19.5% versus 25.3%; P =0.27). Among secondary outcomes, the proportions of patients with sustained ventricular tachyarrhythmia (39.7% versus 48.2%; P =0.050) and appropriate ICD therapy (34.2% versus 47.0%; P =0.020) were numerically reduced in the preventive ablation group. Conclusions: Preventive VT ablation before ICD implantation did not reduce mortality or hospitalization for arrhythmia or worsening heart failure during 1 year of follow-up compared with the deferred ablation strategy. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02501005. Abstract : Supplemental Digital Content is available in the text.